Coxiella burnetii infection in the lumbar vertebra: a rare case report and review of literature - Tan, Xingguo; Li, Feng; Zhang, Tao; Song, Mingjia; Zhang, Lian; Xing, Yuan; Wang, Yizhe; Chen, Long; Huang, Dashuai; Lu, Yanpeng; Li, Songkai (Frontiers in Medicine, 2025)
Coxiella burnetii is a bacterial pathogen of Q fever. Coxiella burnetii infection in the lumbar vertebra is a rare form of chronic Q fever, which poses significant obstacles in both diagnostic processes and therapeutic interventions. A 57-year-old male patient with a previous diagnosis of lumbar infection with unknown pathogen at another institution was admitted for treatment. At our institution, the patient underwent surgical interventions, including decompression through total laminectomy, lesion excision, intervertebral bone graft fusion, and fixation. Intraoperative pathological samples were analyzed using a specific multiplex quantitative polymerase chain reaction (qPCR) pathogenic microorganism detection, confirming the presence of Coxiella burnetii. Postoperatively, the patient received long-term antibiotic therapy by oral doxycycline and ciprofloxacin for a duration plan of 18 months. At the 6-month post-operative evaluation, the patient exhibited complete resolution of clinical symptoms, and imaging results revealed no evidence of infection recurrence, suggesting a clinical cure. The combination of decompression through total laminectomy, lesion excision, intervertebral bone graft fusion, and fixation alongside oral doxycycline and ciprofloxacin treatment has been demonstrated to be an effective therapeutic strategy for managing Coxiella burnetii infection in the lumbar vertebra.